LRRK2 regulates retrograde synaptic compensation at the Drosophila neuromuscular junction - Jay Penney (Nature Portfolio, 2016)
Mutations in the protein LRRK2 have been associated with Parkinson's disease but little is still known about the basic functions of the protein in the brain. Here the authors show that in fruit flies, LRRK2 regulates retrograde homeostatic synaptic compensation at the larval neuromuscular junction.